Dietary Trehalose Activates Autophagy Potentially Via MAPK Signaling Pathway to Alleviate Oxidative Stress Induced by Air Exposure Stress in Chinese Mitten Crab (Eriocheir sinensis) - Anjun Xiang; Jiayi Chen; Jianyang Sun; Chengyi Weng; Yongxu Cheng; Xiaozhen Yang (Aquaculture Nutrition)
Air exposure stress (AES) is a common stress faced by Chinese mitten crabs (Eriocheir sinensis) in aquaculture and transport. This study was designed to evaluate the levels of endogenous trehalose, oxidative stress, and autophagy in crabs subjected to AES (0, 24, and 48 h) after 14 days of feeding diets with different levels of trehalose (Diet1, 0 g/kg; Diet2, 1 g/kg; Diet3, 5 g/kg; and Diet4, 10 g/kg). The results showed that after AES, the endogenous trehalose in crabs was significantly reduced, the expression of trehalose hydrolase (TREH) gene were significantly downregulated, while trehalose-6-phosphate synthase (TPS) gene and trehalose transporters (TRET) gene were remarkably upregulated. These results showed that crabs exhibited an increased demand for trehalose under AES. AES induced oxidative stress damage in the hepatopancreas of crabs resulting in hepatic tubules atrophy, increased vacuolated cells, significantly increased catalase (CAT) activity and malondialdehyde (MDA) content, and decreased superoxide dismutase (SOD) activity. Dietary trehalose supplementation significantly upregulated the expression of TREH gene in crabs, significantly downregulated the expression of TPS gene, and notably enhanced trehalose content. Dietary supplementation with trehalose mitigated hepatopancreatic oxidative damage in crabs subjected to AES. At 48 h of AES, the hepatopancreas of the Diet4 group maintained histological normality, with significantly decreased CAT activity and MDA content, and significantly increased SOD activity. Notably, the protective effect of trehalose may be attributed to its activation of autophagy. Dietary trehalose supplementation significantly upregulated the expression of autophagy-related genes (ATG4B, ATG7, ATG13, and Beclin1) and canonical autophagic MAPK signaling cascade (ERK, JNK, and p38), with p38 protein results further indicating potential activation of this pathway. These findings indicated that dietary trehalose supplementation influences the regulation of endogenous trehalose in crabs, potentially modulating autophagy via the MAPK signaling pathway to alleviate oxidative stress induced by AES.